Flip-Flow bioreactors enhance bioproductions with better oxygen transfer and energy saving - Ge Zhang; Manuel Tianchen Tang; Chao Li; Yongqiang Liu; Wanze Wang; Weike Guo; Xueqing Yi; Yiling Chen; Xuanming Xu; Fuqing Wu; Guo-Qiang Chen (Bioresource Technology, 2026)

Effects of carriers and addition modes on the physical and chemical properties of green pepper (Piper nigrum L.) powders treated by freeze-far infrared drying during storage - Xinyi Wang; Yiling Tang; Yue Huang; Hui Su; Xiaoyu Fan; Hongchen Li; Haiming Chen; Ming Zhang; Jianfei Pei; Congfa Li; Wenxue Chen; Ying Lyu (Food Chemistry, 2026)

A novel strategy for targeted enzymatic deacidification of high-acid rice bran oil using immobilized monoacylglycerol lipase - Xuan Liu; Yiling Tang; Weifei Wang; Hao Fang; Dongming Lan; Yonghua Wang (Food Chemistry, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

Toward a comprehensive map of Rab-mediated cargo transport to migrasomes - Yiling Wen; Yong Li; Jiayi Chen; Dianxing Liu; Yuanchao Li; Ying Li; Haohao Tang; Peizhen Gao; Wenmin Tian; Ning Shen; Yang Chen (Science China Life Sciences, 2026)

Comprehensive Analysis of the R2R3-MYB Transcription Factor Gene Family in Salvia miltiorrhiza and the Regulatory Role of SmMYB50 in Salvianolic Acid Metabolism - Huiyan Fan; Jingzhi Zhou; Yiling Ying; Kaijie Tang; Jiayi Han; Qiuying Wang; Guoyin Kai (Plant Molecular Biology Reporter, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

Generation and distribution of cyanide in rats and humans following sodium cyanoborohydride exposure - Zhenshuo Guo; Yiling Tang; Ruilin Zhang; Yu Ma; Ruxin Luo; Ping Xiang; Hui Yan; Wenjia Duan (Toxicology and Applied Pharmacology, 2025)

Tannic acid: A star molecule in the construction and biomedical applications of hydrogels - Wei Zhang; Yiling Chen; Jing Huang; Ziyi Xiao; Fangjing Wang; Guihui Zhu; Xinying Liao; Yuxin Tang; Zhihao Song; Jian Sun; Yang Liu (Chemical Engineering Journal, 2025)

Endoplasmic reticulum stress regulates swainsonine-induced the autophagy in renal tubular epithelial cells through UPR signaling pathway - Lihui Tang; Shuhang Zhang; Yichao Zhai; Kexin Wu; Pan Wang; Yiling Liu; Congcheng Zhang; Hai Yin; Yanan Tian; Baoyu Zhao; Hao Lu (Science of The Total Environment, 2025)

Metabolism study of two phenethylamine − derived new psychoactive substances using in silico, in vivo, and in vitro approaches - Yiling Tang; Linhao Xu; Zhenshuo Guo; Junbo Zhao; Yue Xiao; Ping Xiang; Lili Xu; Hui Yan (Archives of Toxicology, 2025)

Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

A multi-strategy self-adaptive differential evolution algorithm for assembly hybrid flowshop lot-streaming scheduling with component sharing - Yiling Lu; Qiuhua Tang; Shujun Yu; Lixin Cheng (Swarm and Evolutionary Computation, 2025)

Dual-CRISPR/Cas12a-assisted RT-RAA visualization system for rapid on-site detection of nervous necrosis virus (NNV) - Jie Gao; Siyou Huang; Jing Jiang; Qijin Miao; Rui Zheng; Yiling Kang; Wanting Tang; Hongliang Zuo; Jianguo He; Junfeng Xie (Analytica Chimica Acta, 2025)

Disruption of network hierarchy pattern in bulimia nervosa reveals brain information integration disorder - Yiling Wang; Lirong Tang; Jiani Wang; Weihua Li; Miao Wang; Qian Chen; Zhenghan Yang; Zhanjiang Li; Zhenchang Wang; Guowei Wu; Peng Zhang (Appetite, 2024)

GMPR2-MDA5 interaction bridged the cell junction and anti-GCRV immune - Mingxue Sun; Yiling Li; Hao Tang; Wei Duan; Yijing Liao; Tiaoyi Xiao; Yaoguo Li (Aquaculture, 2024)

A multifunctional hydrogel with mild photothermal antibacterial and antioxidant properties based on quercetin and dopamine-coated zinc oxide nanoparticles for healing bacteria-infected wound - Yan Liu; Qinbin Ma; Lei Tang; Yiling Shen; Huancai Zhao; Xiaoxu Liu; Danqi Lin; Guiyin Zhou (Chemical Engineering Journal, 2024)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Recombinase-aided amplification coupled with lateral flow dipstick for efficient and accurate detection of Bombyx mori nucleopolyhedrovirus - Runpeng Wang; Sheng Xu; Erjun Wei; Ping He; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2024)

Autophagic-lysosomal damage induced by swainsonine is protected by trehalose through activation of TFEB-regulated pathway in renal tubular epithelial cells - Shuhang Zhang; Hai Yin; Yiqingqing Zhang; Yanli Zhu; Xueyao Zhu; Wenting Zhu; Lihui Tang; Yiling Liu; Kexin Wu; Baoyu Zhao; Yanan Tian; Hao Lu (Chemico-Biological Interactions, 2024)

LDH nanocrystal@amorphousness core–shell structure derived from LDH → LDO transformation: Synergistically enhanced energy stored for LIBs anode - Kai Yang; Yiling Huang; Peixing Wang; Yixuan Tang; Yiwen Zhu; Xiaoxue Zhu; Yan Xu; Wei Jiang; Limei Pan; Qian Li; Haijiao Xie; Jian Yang (Chemical Engineering Journal, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

A catastrophic high-speed train crash caused by a small-scale debris flow in China - Shuai Zhang; Cong Dai; Shuairong Wang; Bijiao Wang; Yiling Zhou; Yanbo Chen; Bate Bate; Liangtong Zhan; Yunmin Chen; Yao Tang (Transportation Geotechnics, 2023)

Afidopyropen suppresses silkworm growth and vitality by affecting carbohydrate metabolism and immune function - Erjun Wei; Ping He; Runpeng Wang; Sheng Xu; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Pesticide Biochemistry and Physiology, 2023)

Development of an LC-MS/MS method for the determination of multiple mycotoxins in human urine - Mobing Chen; Wei Liu; Ping Xiang; Linhao Xu; Yiling Tang; Ran Kong; Shuo Yang; Hui Yan; Bin Di (Food Additives & Contaminants: Part A, 2023)

Fatal landslides in China from 1940 to 2020: occurrences and vulnerabilities - Shuai Zhang; Can Li; Jingyu Peng; Yiling Zhou; Shuairong Wang; Yunmin Chen; Yao Tang (Landslides, 2023)

Elucidation of the GAUT gene family in eight Rosaceae species and function analysis of PbrGAUT22 in pear pollen tube growth - Yiling Cai; Chao Tang; Shouzheng Lv; Qiming Chen; Xiaoxuan Zhu; Xian Li; Kaijie Qi; Zhihua Xie; Shaoling Zhang; Peng Wang; Juyou Wu (Planta, 2023)

Swainsonine-induced vacuolar degeneration is regulated by mTOR-mediated autophagy in HT22 cells - Yanbing Liu; Shuhang Zhang; Weina Wang; Shiyu Tang; Yiru Zhu; Meng Wang; Bingqian Cao; Yanli Zhu; Lihui Tang; Yiling Liu; Chonghui Mo; Baoyu Zhao; et al. (Toxicology Letters, 2023)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Use of DNA nanosensors based on upconverting nanoparticles for detection of Nosema bombycis by fluorescence resonance energy transfer - Ping He; Hongli Chen; Jiancheng Sun; Qiang Wang; Xudong Tang; Yiling Zhang; Feng Zhu; Zhongyuan Shen (Folia Microbiologica, 2022)

Nitrogen-cycling genes and rhizosphere microbial community with reduced nitrogen application in maize/soybean strip intercropping - Lingling Yu; Yiling Tang; Zhiguo Wang; Yonggang Gou; Jianwu Wang (Nutrient Cycling in Agroecosystems, 2019)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Isolation and characterization of a novel cDNA encoding methyl jasmonate-responsive transcription factor TcAP2 from Taxus cuspidata - Yiling Dai; Qiulin Qin; Dalin Dai; Lisheng Kong; Wei Li; Xiaojun Zha; Yuanjie Jin; Kexuan Tang (Biotechnology Letters, 2009)